Curriculum Management Practices in Pesantren-Based Education for Students' Character Development - Fika Wahdatul Ummah; Poppy Rachman; Arifia Retna Yunita (Journal of Educational Management Research, 2026)
This study aims to analyze the implementation of pesantren-based curriculum management in fostering students' character within an Islamic boarding school. A qualitative approach employing a case study design was adopted to obtain an in-depth understanding of curriculum management practices. Data were collected through observations, semi-structured interviews, and document analysis involving school leaders, teachers, boarding administrators, and students. Data analysis followed the stages of data reduction, data display, and conclusion drawing, while the trustworthiness of the findings was ensured through source and technique triangulation. The findings reveal that pesantren-based curriculum management is implemented through integrated curriculum planning that combines formal and religious education within a twenty-four-hour boarding system, systematic implementation of religious, academic, and character-building activities, and continuous evaluation through attendance records, student monitoring, and direct supervision. These practices effectively cultivate students' religious values, discipline, independence, responsibility, humility, and social awareness through sustained habituation and exemplary role modeling. The study implies that integrating formal education with pesantren values through comprehensive curriculum management provides an effective framework for strengthening character education and may serve as a reference for developing value-based curriculum management in other Islamic boarding schools.